Nonlinear optical properties DFT calculations of polyacethylene and copolymers models substituted with aldimines chromophores as side chains. Issue 25 (8th August 2022) - Benchehaima, Fatima‐Zohra; Springborg, Michael; Rahal, Majda Sekkal
Abstract: Aldimine derivatives chromophores grafted on polyacetylene oligomers were first designed to investigate the nonlinear optical (NLO) response of the resulting materials using CAMB3LYP method. The effects of different factors such as the chain length separating the substitutions as well as the configurations and the orientations of these latter, were examined and discussed. In a second part of this paper, NLO responses, in particular the static hyperpolarizabilities of polyvinyl oligomers substituted by aldimine chromophores via carboxylic groups and by pyrrolidone groups were calculated for different configurations. The stability and the hydrogen bonding in each oligomer were also discussed. Abstract : Structure and hydrogen bonding of the oligomer with n  = 2 and m  = 2, giving the best hyperpolarizability.